DETERMINAN STRUKTUR MODAL (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Alien Akmalia; Farah Amiroh Mamduhah (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2019)
This study aims to examine the determinant of capital structure . The determinant used in this study were profitability, asset growth, company size, and sales growth. Furthermore, this study was carried out by manufacture company which were listed in Indonesia Stock Exchange along the period 2013-2017. The sampling technique used in this study was purposive sampling which obtained as many as 480 data of manufacture companies. The analysis technique of this study using multiple regression analysis. The result showed that profitability has negative significant effect on the capital structure, asset growth and sales growth has positive significant effect on the capital structure. Meanwhile, company size has no significant effect on the capital structure.